A Poet’s Guide to Dylan Thomas - Owen Sheers (http://www.bbc.co.uk/programmes/p01wtzqk, 2014)
1 hour BBC documentary written and presented by Owen Sheers, broadcast on BBC One Wales and BBC Four network.